Analisis Risiko Kredit PT Mitra Adiperkasa Tbk Menggunakan Pendekatan Z-Score Altman - Melda Haulia; Dalizanolo Hulu (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the credit risk of PT Mitra Adiperkasa Tbk using the Altman Z-Score approach as a tool to assess the company’s financial health and potential bankruptcy risk. The research is motivated by the dynamic conditions of the retail industry, which are influenced by economic fluctuations, changes in consumer behavior, and increasing competitive pressure. This study employs a descriptive quantitative research method using secondary data derived from the published financial statements of PT Mitra Adiperkasa Tbk. The analysis is conducted by calculating financial ratios that constitute the Altman Z-Score model and interpreting the results based on the classification criteria of the safe zone, grey zone, and distress zone. The results indicate that PT Mitra Adiperkasa Tbk is categorized in the safe zone, suggesting that the company is in a relatively healthy financial condition with a low risk of bankruptcy. However, external challenges remain and may potentially affect the company’s financial performance in the future. This study is expected to provide useful insights for management, investors, and other stakeholders in evaluating credit risk and supporting strategic decision-making to ensure business sustainability.